Health Hazards Exposure and Health Quality of Radiology Department Personnel in Negros Oriental: A Correlational Study - Caldito, Mark Anthony (International Journal of Sustainability and Advanced Integrated Research, 2026)
This study examined the health quality of radiology department personnel in Negros Oriental in relation to sociodemographic factors, radiation dose exposure, stress factors and work environment, and health hazard exposure. It was anchored on complementary perspectives emphasizing occupational radiation risk, health vulnerability, workplace demands and resources, and the biopsychosocial nature of health. Using a quantitative correlational design, the study was conducted in free-standing, public, and private healthcare facilities in Negros Oriental and involved 56 radiology department personnel, including Radiologic Technologists, X-ray Technologists, Radiologists, Receptionists, and other radiology staff. Data were gathered through a structured questionnaire, radiation badge monitoring, physical or medical examination records, and standardized tools such as the Maslach Burnout Inventory and Job Content Questionnaire. Descriptive statistics, Pearson’s r, and Chi-square tests of independence were used in the analysis. Findings showed that most sociodemographic variables were not significantly associated with health quality, although smoking was significantly related to sick leave, while alcohol drinking was significantly related to both sick leave and number of absences. Annual cumulative radiation dose exposure was low, with a mean of 0.289 mSv, and was not significantly associated with years of operating radiation-producing machines or machine type. Overall stress factors and work environment were not significantly associated with sick leave, but selected workplace stressors, including lack of management support, traumatic experience, job insecurity, lack of proper resources, and discrimination, were significantly related to number of absences. Exposure to chickenpox, measles, and tuberculosis was significantly associated with sick leave, but not with number of absences. The study concluded that health quality among radiology personnel was influenced more by selected behavioral, psychosocial, and infectious hazard factors than by most demographic or equipment-related variables. It recommended continued health protection, consistent use of radiation protective equipment, strict workplace safety compliance, and improved human resource conditions in radiology departments. The study is aligned with SDG 3 (Good Health and Well-Being), SDG 8 (Decent Work and Economic Growth), and SDG 9 (Industry, Innovation and Infrastructure) because it addresses occupational health, safe working conditions, and responsible use of radiation-producing technologies in healthcare settings. Its sustainability impact lies in strengthening public health protection, institutional safety practices, and workplace conditions that support the continuity and quality of radiologic services.